PENGARUH KESEJAHTERAAN DAN FASILITAS TERHADAP MOTIVASI KERJA KARYAWAN DI PT. TIMUR JAYA COLDSTORAGE MEDAN - Tamrin Hasibuan (JRMB (Jurnal Riset Manajemen & Bisnis), 2018)
The work infrastructure is provided by the company for its employees as working facilities. It is compulsory to the company to facilitate the employees to carry out their daily operational activities. The welfare is also one of the means given by the company to its employees aiming at maintaining and improving their physical and mental condition so that they can work better, more skill and productive. Based on this view the study was conducted to see further how the is the influence of facilities and welfare to the employees’ work motivation. This research was conducted at PT. East Jaya Coldstorage Medan using quantitative method involving a number of sample which is 67 people. The data obtained through questionnaire is analyzed through multiple linear regression approach. The result R Square for Y (employee work motivation) is 0.482, and it means that it is significant for variable Y (employee work motivation) and it is influenced by variable X1 (facility) and variable X2 (welfare). In other words, simultaneously the influence of facility (Xl) and welfare (X2) to variable Y (employee work motivation) is 48.2% and the rest is 51.8% determined by other variables beyond the contribution of this research. Similarly, based on partial analysis, it shows that t value which is obtained by 1,937 and this value is significant at a = 0,5% indicating that each variable (X1 and X2) gives effect to the independent variable (Y).